2016
DOI: 10.3748/wjg.v22.i34.7787
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluorodeoxyglucose positron emission tomography/computed tomography comparison of gastric lymphoma and gastric carcinoma

Abstract: AIMTo compare 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) features in gastric lymphoma and gastric carcinoma.METHODSPatients with newly diagnosed gastric lymphoma or gastric carcinoma who underwent 18F-FDG PET/CT prior to treatment were included in this study. We reviewed and analyzed the PET/CT features of gastric wall lesions, including FDG avidity, pattern (focal/diffuse), and intensity [maximal standard uptake value: (SUVmax)]. The correlation of SUVmax with gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
(55 reference statements)
0
13
0
Order By: Relevance
“…[ 14 16 ] Semi-quantitatively, the standard uptake value (SUV) and its derivatives, which correlate to the degree of FDG uptake in tissues, have been demonstrated to help differentiate gastric cancer from gastric lymphoma. [ 17 , 18 ] Nonetheless, FDG uptake has a wide range in both gastric cancer and gastric lymphoma, [ 15 , 17 , 19 ] which is partially due to the differences between pathological subtypes. Therefore, the differential diagnostic accuracy based on only SUV and its derivatives is moderate.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 16 ] Semi-quantitatively, the standard uptake value (SUV) and its derivatives, which correlate to the degree of FDG uptake in tissues, have been demonstrated to help differentiate gastric cancer from gastric lymphoma. [ 17 , 18 ] Nonetheless, FDG uptake has a wide range in both gastric cancer and gastric lymphoma, [ 15 , 17 , 19 ] which is partially due to the differences between pathological subtypes. Therefore, the differential diagnostic accuracy based on only SUV and its derivatives is moderate.…”
Section: Introductionmentioning
confidence: 99%
“…Sun Gaofeng et al [25] studied the PET/CT results of 43 patients with gastric cancer and patients with primary gastric lymphoma and found that there was a difference in SUVmax between them, and the P < 0.05. Similarly, Li XF [26] et al retrospectively analysed 73 cases of gastric cancer and 52 cases of gastric lymphoma, and found that compared with gastric cancer, the results of PET/CT examination of gastric lymphoma were different, and higher SUVmax suggested that gastric lymphoma was more likely. The above results are consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The other 8 cases were misdiagnosed, half of these were localized in the gastrointestinal tract, putatively due to the speci c FDG uptake pattern of lymphoma in the gastrointestinal tract and this phenomenon is consistent with many previous studies that primary gastrointestinal lymphoma is a speci c type of digestive system tumor and its FDG uptake pattern is more likely to have low intake due to physiologic FDG activity in the gastrointestinal tract although variability in the degree of uptake occurred in various histologic subtypes of primary gastrointestinal lymphoma [17,20,21]. Hwang et al also con rmed that SUV max can be used as a prognostic marker for gastrointestinal lymphoma as it differed markedly from other gastrointestinal cancers and is one of the reliable differential diagnostic criteria [22,23]. However, the disease is insidious in onset and still easy to be misdiagnosed and missed in the examination; In this study, two of the misdiagnosed cases were misdiagnosed as in ammation, while the remaining were misdiagnosed as other tumors.…”
Section: Discussionmentioning
confidence: 99%